Emergency medical care for multiple sclerosis: A five-year population study in the Campania Region (South Italy). (April 2022) - Moccia, Marcello; Affinito, Giuseppina; Ronga, Bruno; Giordana, Roberta; Fumo, Maria Grazia; Lanzillo, Roberta; Petracca, Maria; Carotenuto, Antonio; Triassi, Maria; Brescia Morra, Vincenzo; Palladino, Raffaele
Background: Emergency hospital admissions are common in multiple sclerosis (MS), and can highlight unmet medical needs. Objectives: To evaluate burden, predictors and outcomes of MS emergency admissions. Methods: This is a population-based study, conducted in the Campania Region (South Italy) from 2015 to 2019, using hospital discharge records, drug prescriptions and outpatients. The risk of emergency hospital admissions and the likelihood of worse outcomes were evaluated using the Cox regression and multinomial logistic regression models, respectively, in relation to age, sex, disease-modifying treatments (DMTs), comorbidities and adherence. Results: We recorded 1225 emergency admissions for 1001 patients (out of 5765 prevalent MS patients), overall costing 4, 143, 764.67 EUR. The risk of emergency admissions increased with age (hazard ratio (HR) = 1.02; 95% confidence interval (CI) = 1.01, 1.03; p  < 0.01) and comorbidities (HR = 1.62; p  < 0.01), and decreased in patients using DMTs (interferon beta/peg-interferon beta/glatiramer acetate HR = 0.19; p  < 0.01; teriflunomide/dimethyl-fumarate/fingolimod HR = 0.18; p  < 0.01, and alemtuzumab/cladribine/natalizumab/ocrelizumab HR = 0.21; p  < 0.01), and with higher adherence (HR = 0.18; 95% CI = 0.13, 0.26; p  < 0.01). Following emergency admission, older age was associated with probability of death ( n  = 63) (odds ratio (OR) = 1.06; p  < 0.01) and discharge to long-term facility ( n  = 65) (OR = 1.03; p  = 0.01). Conclusion: With 17% people with MS requiring emergency medical care over 5 years, improved management of DMTs and comorbidities could potentially reduce their medical, social and financial burden.